Phosphonosulfonates Are Potent, Selective Inhibitors of Dehydrosqualene Synthase and Staphyloxanthin Biosynthesis in Staphylococcus aureus - Song, Yongcheng (2009)
Staphylococcus aureus produces a golden carotenoid virulence factor called staphyloxanthin (STX), and we report here the inhibition of the enzyme, dehydrosqualene synthase (CrtM), responsible for the first committed step in STX biosynthesis. The most active compounds are halogen-substituted phosphonosulfonates, with K(i) values as low as 5 nM against the enzyme and IC(50) values for STX inhibition in S. aureus as low as 11 nM. There is, however, only a poor correlation (R(2) = 0.27) between enzyme and cell pIC(50) (= −log(10) IC(50)) values. The ability to predict cell from enzyme data improves considerably (to R(2) = 0.72) with addition of two more descriptors. We also investigated the activity of these compounds against human squalene synthase (SQS), as a counterscreen, finding several potent STX biosynthesis inhibitors with essentially no squalene synthase activity. These results open up the way to developing potent and selective inhibitors of an important virulence factor in S. aureus, a major human pathogen.